2018
DOI: 10.5830/cvja-2018-009
|View full text |Cite
|
Sign up to set email alerts
|

Levitronix bilateral ventricular assist device, a bridge to recovery in a patient with acute fulminant myocarditis and concomitant cerebellar infarction

Abstract: We report on the case of a 27-year-old male who presented to our emergency room with chest tightness, dyspnoea and cold sweats. The 12-lead electrocardiogram showed diffuse ventricular tachycardia with wide QRS complexes. Troponin-I level was elevated to 100 ng/ml. The coronary angiogram showed good patency of all three coronary vessels, and acute fulminant myocarditis was suspected. The patient underwent cardiopulmonary resuscitation in the catheter room and high-dose inotropic support was initiated to stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, ineligibility for the procedure or a shortage of donor organs may require an alternative, i.e., long-term MCS systems. In many reports, VAD systems were used as a bridge to recovery or transplantation, and patients with persistent biventricular failure were successfully treated with Bi-VADs [ 19 , 27 , 70 , 71 ]. It is recommended to consider early examinations for transplant and VAD evaluation to avoid subsequent delay in case of unsuccessful weaning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, ineligibility for the procedure or a shortage of donor organs may require an alternative, i.e., long-term MCS systems. In many reports, VAD systems were used as a bridge to recovery or transplantation, and patients with persistent biventricular failure were successfully treated with Bi-VADs [ 19 , 27 , 70 , 71 ]. It is recommended to consider early examinations for transplant and VAD evaluation to avoid subsequent delay in case of unsuccessful weaning.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the reported cases, a left ventricular assist device (LVAD) was utilised and served as a bridge to transplant, recovery, or destination therapy. However, selected patients might require a bilateral ventricular assist device (Bi-VAD) [ 70 ]. Jaroszewski et al even reported a patient with FM who underwent ECMO and was bridged to temporary Bi-VAD, followed by permanent VAD systems, and eventually, recovery [ 71 ].…”
Section: Epidemiology Of Myocarditismentioning
confidence: 99%